“LAS PALABRAS VUELAN, LO ESCRITO SE QUEDA” (THE WORDS FLY, THE WRITTEN STAYS): THE JUDEO-SPANISH (HAKETIC) PROVERB IN NORTHERN MOROCCO - Alexander, Tamar; Bentolila, Yaakov (Proverbium - Yearbook, 2014)
The aim of this article is to define the literary and linguistic characteristics of proverbs in Haketia in order to examine the proverb as an expression of ethnic identity. Haketia is the Judeo-Spanish lan-guage spoken in Jewish communities in northern Morocco among de-scendants of Jews exiled from Spain. We claim that the tradition of proverbs in Haketia possesses its own unique characteristics that ex-press the “voice of the group.” To isolate this voice, we analyzed prov-erbs in Haketia in comparison to their counterparts in other groups that belong to the same cultural context: (1) Proverbs from canonical He-brew sources (Bible, Talmud, and Midrash) that are commonly shared within the whole Jewish culture. (2) Spanish proverbs: The affinities with the culture of their geographical origin (Spain) that is shared among all the communities that speak the Judeo-Spanish language; Modern Spanish had a decisive effect among Haketia speakers. (3) An-other Judeo-Spanish group: the eastern Ladino speakers (we chose Sa-lonika). (4) The Judeo-Arabic speakers in Morocco, and Muslims speaking Moroccan Arabic with whom the speakers of Haketia inter-acted on a daily basis. (5) Finally, we examined unique proverbs in Haketia for which we could not find a counterpart in other cultures. For every group we posed a different secondary research question (such as theme, genre, language, or context) and offered a different method of research using analytical tools taken from different disciplines, such as literature, folklore, linguistics, and history.